2005
DOI: 10.1007/s10562-005-6522-6
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of a Pd/γ-alumina Catalyst During Methane Combustion: Investigation of the Phenomenon and of Potential Causes

Abstract: Activation phenomena of a Pd/c-Al 2 O 3 catalyst under methane combustion reaction conditions were studied. The activation of the catalyst with time-on-stream is not due to Cl removal from the surface but seems to be related to sintering of the palladium particles. This could induce structural changes in the palladium particle, which would favor the activation of O 2 on the surface of PdO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
2
21
0
1
Order By: Relevance
“…Previous results demonstrated that the XPS surface Pd/Al atomic ratio can be used as a relevant indicator of the dispersion of palladium on the alumina support [25]. It can be considered that for the Pd/Al atomic ratio a variation >than 5% is significant An important decrease of the XPS Pd/Al atomic ratio can be observed after test without H 2 in the feed (À18%), as already mentioned in earlier works [23,25,31]. This effect is significantly reinforced in presence of hydrogen (À28%), independently of its concentration (up to 10 vol.% H 2 ), in agreement with data obtained in the case of the 2 wt.%-loaded catalyst [23].…”
Section: Bet Co-chemisorption and Xpssupporting
confidence: 51%
“…Previous results demonstrated that the XPS surface Pd/Al atomic ratio can be used as a relevant indicator of the dispersion of palladium on the alumina support [25]. It can be considered that for the Pd/Al atomic ratio a variation >than 5% is significant An important decrease of the XPS Pd/Al atomic ratio can be observed after test without H 2 in the feed (À18%), as already mentioned in earlier works [23,25,31]. This effect is significantly reinforced in presence of hydrogen (À28%), independently of its concentration (up to 10 vol.% H 2 ), in agreement with data obtained in the case of the 2 wt.%-loaded catalyst [23].…”
Section: Bet Co-chemisorption and Xpssupporting
confidence: 51%
“…In previous studies [41,42], we have also observed sintering of the palladium phase during the CCM process, which leads to more active catalysts. Some researchers also suggested that large palladium crystallites catalyze the CCM reaction more effectively than highly dispersed palladium particles [1,23,[43][44][45][46][47][48][49][50].…”
Section: Influence Of H 2 Upon the Pd/g-al 2 O 3 Catalystmentioning
confidence: 69%
“…[11,12] The partial reduction of Co 3 + to Co 2 + in perovskite leads to large amounts of active sites (oxygen vacancies) for oxygen adsorption and, thus, a high catalytic activity towards methane oxidation. [14] When comparing the fresh (Figure 2 d) and spent (Figure 6 a) one can see that the spent coating contains spherical particles of about 100-200 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Cobalt-containing perovskites and noble-metal Pd catalysts are known for their activity towards methane combustion. [11] The noble-metal, Pd-modified perovskites are expected to combine the advantages of the above two kinds of catalysts, namely, catalytic activity and thermal resistance. In addition, it was reported that the presence of Pd can increase the reducibility of cobalt ions in Pd-Co/Al 2 O 3 , [12] which leads to a better catalytic performance for methane oxidation.…”
Section: Introductionmentioning
confidence: 99%